EFEKTIVITAS SISTEM LOSI OLEH UNIT AVSEC DALAM PENANGANAN BARANG TERCECER DI AREA LANDSIDE - Fryda Fatmayati; M Sobur Burhanudin (Jurnal Manajemen Dirgantara, 2024)
Air transport is very important for Indonesia, because the condition of Indonesia which has many islands, air transport can connect between islands in a fairly fast and efficient time. One aspect that greatly affects air transport activities is the availibility of airports. Airports have facilities and infrastructure to support various airport activities at each airport in Indonesia. Not only passangers who need good facilities and handling, but also the handling of their goods. One of them is the Aviation Security (AVSEC) officer who handles lost items found in the airport landside area. The purpose of this study is to determine the use of the information system Lost Item (LOSI) is effective or not in handling scattered passanger goods, how much the effectiveness of the Lost Item (LOSI) application information system, and to find out the obstacles faced. In this study the authors used mixed methods, namely combining quantitative and qualitative methods to be used together in one study, so as to obtain more valid and reliable, and objective data. The data used for this research are questionnaires, interviews, observations and documentation. The author can explain that the use of the LOSI application information system carried out by the Aviation Security unit is effective for handling scattared passanger goods, this means that the Ho hypothesis is rejected and Ha is accepted. Furthermore, in the T test results form the coefficient table, it can be seen that there is a significant effectiveness between the independent variable X (effectiveness of using the LOSI application) on the dependent variable Y (handling of scattered passanger items) with the results of the calculation of the coefficient of determination (R)2 geeting a value of 66,4% and the remaining 33,6% is influenced by other factors that researchers do not discuss in this study. Obstacles faced in the procedure for handling the Lost Item Information System in the LOSI application to deal with scattered passanger itmes, namely, technical obstacles such as network disruptions, constraints and communication systems.